Consumers’ Repurchase Intention towards Counterfeit Products - Kaiyethire Bupalan; Suzari Abdul Rahim; Aidi Ahmi; Nor Aida Abdul Rahman (International Journal of Supply Chain Management, 2019)
Nowadays, it hardly recognises the differences between a genuine and counterfeit product as the imitation products have flooded the market all over the world. In recent years, information technology and e-commerce have influenced the business market to produce fake products online, and products were produced with cheaper quality. In reality, they are many individuals who look up and purchase counterfeit products. Counterfeit products have been observed to be a significant issue around the world that destroy economic exercises as well as it influences social life. Therefore, this study aims to identify the determinants that influence the repurchase intention towards counterfeit products among consumers’ using the Theory of Planned Behaviour (TPB) framework. Data was collected via questionnaire from 114 consumers’ based in Penang, Malaysia. The final results indicate that attitude, perceived behavioural control, product involvement and brand image are crucial determinants affecting purchase intention towards counterfeit products. Meanwhile, brand image was found significantly mediates the relationship between product involvement and repurchase intention of counterfeit products. By having a better understanding of the consumers’ behavioural intentions of purchasing or repurchasing counterfeit products, the owner of the genuine brand products can produce better products and make better sales and marketing strategies to entice the customer to purchase their original products.